Pengaruh Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pembelian Konsumen Pada Situs Belanja Online Lazada (Studi kasus pada konsumen Mahasiswa Universitas Islam Malang) - Tegar Amirul Huda; M. Khoirul ABS; Agus Widarko (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract In this study, due to the rapid development of technology, especially in the field of social media, this created a golden opportunity for e-commerce companies to expand their reach to consumers. To provide satisfaction in purchasing consumers, there is an increase in the quality of products and services in the company. The purpose of this study is to find out the magnitude of the influence of purchase satisfaction which is influenced by the quality of services and products and data collection is done using the questionnaire method with 100 respondents. The criteria of the respondents are students of Malang Islamic University. By using the validity, reliability, normality test, linear and simple regression test, t-test and F test can give results in the form of an influence between product quality and service on consumer purchasing satisfaction with results of 0.00 and 0.03 and all of them have an influence positive and significant Keywords: Products, Service Quality, Consumer Purchasing SatisfactionKeyword: Product, Quality Of Service,  Consumer Purchasing Satisfaction